Residual effect of organic compost on lettuce growth and yield - Santos, Ricardo Henrique Silva; Silva, Franceli da; Casali, Vicente Wagner Dias; Conde, Alcides Reis (Pesquisa Agropecuaria Brasileira, 2001)
This paper aimed to evaluate the residual effect of organic compost fertilization on lettuce growth and yield. Seedlings of 'Babá' lettuce were fertilized with five doses of organic compost (0.0, 22.8, 45.6, 68.4 and 91.2 ton/ha of dry matter), in the presence and in the absence of mineral fertilizer (643 kg/ha of 4-14-8 plus two side dressings of 30 kg/ha of N). The residual effect was evaluated by carrying out a second cultivation on the same plots with no fertilizer addition after the first cultivation. Fertilization with organic compost increased the second cultivation yield up to 27,367 kg/ha of fresh weight at the highest dose, in plants grown between 80 and 110 days after organic compost application. The mineral fertilization showed no residual effect. The residual effect also resulted in increases in soil exchangeable bases, P, and effective soil cation exchange capacity (CEC) reaching values of 10.77 cmolc/dm3, 461 mg/dm3 and 11.08 cmolc/dm3, respectively.